Surface Tension and Fluid Flow Driven Self-Assembly of Ordered ZnO Nanorod Films for High-Performance Field Effect Transistors. - Sun, Baoquan; Sirringhaus, Henning (Journal of the American Chemical Society, 2006)
Colloidal nanorods of inorganic semiconductors are of interest for a range of optoelectronic devices. The ability to self-assemble these materials into ordered arrays by solution-processing techniques is crucial for achieving adequate device performance. Here we show that uniform ZnO nanorod films with defined nanorod alignment can be solution-deposited over large areas by controlling the surface energy of the nanorods through the choice of suitable ligands and by the fluid flow direction during growth. ZnO nanorods with long carbon chain ligands exhibit a smaller surface free energy than those with short carbon chain ligands resulting in better in-plane alignment and large domain sizes up to dozens of micrometers in spin-coated films. A model is presented to rationalize the observed self-assembly behavior. It is based on the formation of a lyotropic liquid crystalline phase on the surface of the liquid film which is facilitated by enhanced segregation of nanorods with low surface tension to the surface. Alignment of the nanorods is controlled by radial and vertical liquid flows in the drying solution. The ability to control the orientation of the nanorods and to achieve large domain size results in significant device performance improvement. Field-effect transistors with mobilities of up to 1.2–1.4 cm²N·s are demonstrated in spin-coated, in-plane aligned ZnO nanorod films subject to postdeposition hydrothermal growth.